Implementasi E-Commerce Minyak Kemiri BUMDes Inegena Berbasis Web Menggunakan Algoritma Naive Bayes - Theresia Clarita Neba; Anastasia Mude; Krisantus Thomas Rada (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This research aims to address the challenges in sales data management and limited market reach faced by the Inegena Village-Owned Enterprise (BUMDes) in North Bajawa District, Ngada Regency, East Nusa Tenggara. The BUMDes produces and sells candlenut oil, a superior local product, but currently uses a manual sales and recording system (B2B and B2C), which leads to fluctuating demand, difficulties in sales data analysis, and decision-making that lacks valid data. To address these issues, a web-based e-commerce system was implemented. This system was designed using Agile methods, involving planning, implementation, software testing (black box testing), documentation, deployment, and maintenance. Furthermore, the Naïve Bayes algorithm was applied to visualize sales data and support better decision-making by classifying best-selling products, popular payment methods, and sales levels. The results of this research are expected to assist Inegena BUMDes in improving sales efficiency, expanding the market reach of candlenut oil products nationally. This system uses supporting software such as Xampp, PHP, and MySQL.